The Use of Rarangkén Ngalogat at Miftahul Huda Islamic Boarding School in Tasikmalaya: Charles Sanders Peirce's Semiotic Study - Wihandani, Wihandani; Taufiq, Wildan; Riyadi, Hendar; Nugraha, Eghy Farhan (Lughaat: Journal of Arabic Linguistics, 2026)
This study aims to identify the meaning of symbols used in the learning activities of students at Salafi Islamic boarding schools and to understand the application known as Rarangkén ngalogat. Rarangkén ngalogat is a symbol used exclusively by Islamic boarding schools in West Java. This research uses an analytical description method with an interactive analysis model. The approach used was qualitative descriptive. Data collection methods used were interviews, observations, and surveys. This study aimed to uncover the semiosis of rarangken ngalogat using Pierce’s semiosis theory and its use at the Miftahul Huda Islamic boarding school in Tasikmalaya. The theoretical framework of this study is based on Charles Sanders Peirce's semiotic theory, which proposes a trichotomy (representamen, object, and interpretant). The results show that the semiosis of rarangkén ngalogat at the Miftahul Huda Islamic boarding school leads to the sciences of balaghah, manṭiq, naḥw, and the addition of the word ngalogat. Rarangkén ngalogat is practiced during learning activities such as sorogan, bandongan, balagan, and pasaran in accordance with the ibtidā'i, thānawiy, and ma’ḥad ‘āliy levels. The Rarangken ngalogat is rarely used at the elementary level, and translations are sometimes written in Pegon script in classical texts. At the thānawiy level, the rarangken ngalogat becomes more visible and is frequently used, emphasizing its role in improving comprehension. This contrast with the Ma'had 'āliy level, where it is rarely used, underscores its importance. The use of rarangken ngalogat is very beneficial for students because it facilitates their understanding when reading the text.